Activity of Antioxidant and Inhibitor ?-Glucosidase Instant Granul Ethanol Tea Leaf Extract (Camellia sinensis) and Tea Benalu (Scurulla atropurpureea BL Dans) - Bina Lohita Sari; Akhmad Endang Zainal Hasan; Lusi Agus Setiani (Universitas Pakuan, 2018)
Tea leaves are plants that are widely spread especially in the area of West Java, while parasites are parasitic plants in tea trees that empirically have various properties such as antioxidants and anti diabetic. The ?-glucosidase inhibitor is one of the therapeutic drugs for diabetic that works by inhibiting carbohydrate metabolism. Instant granule preparation is one form of dosage used by dissolving in water. This study aims to determine the antioxidant activity and inhibitors of instant granular ?-glucosidase ethanolic extract of Tea and Tea Tea leaves. The extract was obtained from extraction with 60% ethanol solvent-assisted extraction (MAE) method. Research was done by making 3 formula (Formula 1, 2 and 3) with comparison of tea leaf extract, parasite, Polivinil pyrrolidone (PVP) and cyclodextrin ie 26,88%, 1,8%, 2%, 0% (Formula 1) 26.88%, 0%, 3%, 12% and 0% (Formula 2), 1.8%, 4%, 15% (Formula 3). Formula 2 is active as an antioxidant and ?-glucosidase enzyme inhibitor with IC50 values of 68.21 and 56.76 ppm. Keywords: Tea Leaves, Benalu Tea, Antioxidants, ?-glucosidase Inhibitors, Instant Granules